CAZ catalog and optical light curves of 7918 blazar-selected active galactic nuclei - Kouch, Pouya M.; Lindfors, Elina; Hovatta, Talvikki; Liodakis, Ioannis; Koljonen, Karri I. I.; Paggi, Alessandro; Nilsson, Kari; Jormanainen, Jenni; Ramazani, Vandad Fallah; Kankkunen, Sofia; Wierda, Folkert; Wagner, Sarah M.; et al. (EDP Sciences, 2026)
Active galactic nuclei (AGN) are some of the brightest and most variable objects in the Universe. Those with relativistic jets observed at small viewing angles are blazars. Due to Doppler boosting, blazars exhibit extreme stochastic variability. While the origin of this variability is thought to be changes in the accretion flow and jet dynamics, much about blazar variability remains unknown. In this paper we use several blazar-dominated AGN samples to form a catalog of 7918 blazars and candidates - the largest to date. We also collected source types, redshifts, peak frequencies of the spectral energy distribution, radio variability Doppler factors, and X-ray flux densities for as many sources as possible. We used all-sky surveys (CRTS, ATLAS, and ZTF, abbreviated as "CAZ") to extract their optical multiband flux density on a nightly basis between 2007 and 2023, and we constructed as long and as high cadence light curves as possible for as many sources as attainable. We quantified the variability of the light curves and applied the Bayesian blocks algorithm to determine their flaring periods. The CAZ catalog and light curves as well as the corresponding Bayesian blocks and flaring periods are all provided in the accompanying electronic tables, with the goal of enabling analyses involving jetted AGN variability with unprecedented sample sizes. Overall, we find (1) optical flares generally have a faster rise than decay; (2) optical brightness and variability are strongly dependent on the synchrotron peak frequency; (3) flat spectrum radio quasars and BL Lac objects have comparable optical variability and flare characteristics at the same synchrotron peak frequency; and (4) optical flare times tend to decrease while amplitudes increase with an increasing radio variability Doppler factor.